Biocycle between Design and Additive Manufacturing. Issue 1 (16th April 2021) - Scognamiglio, Ciro; Capece, Sonia; De Luca, Alessandro; Amendola, Eugenio; Egido‐Villarreal, Janitzio; Buono, Mario
Abstract: The paper describes the experience of research and experimentation conducted for the configuration of a new "Biocycle" bike conceived through eco‐friendly and bio‐inspired design methods and with the support of additive manufacturing (AM) technologies aimed to achieve a customized and flexible production. According to this logic, it is necessary to consider the AM as a valid support to both innovation and growth of many sectors in which creativity and design capacity play a strategic role for original solutions. The multidisciplinary approach and the collaboration between research institutes, companies, laboratories and universities, characterize the design and experimentation of the Biocycle. This has enabled the development of a new bicycle according to eco‐design and bio‐design criteria, by using recycled materials such as polyethylene terephthalate (PET), by introducing the principles of the environmental design into the definition of the entire product life cycle and by merging traditional production methods with AM to optimize the performance and reduce the overall weight, costs, and production time of the frame. To support the design phase, also a finite element (FE) model was developed. The aim is to obtain lightweight performing components with compact and ergonomic dimensions for the eco‐bike. This leads to the synthesis of new unconventional shapes and a better distribution of the material from the topological‐functional optimization analysis as well as AM.